Tooth-Derived Granules in Combination with Platelet-Rich Fibrin ("Sticky Tooth") in Socket Preservation: A Histological Evaluation - Andreas van Orten; Werner Goetz; Hakan Bilhan (MDPI AG, 2022)
Background: The maintenance of ridge volume following tooth extraction has gained more importance in the last few years. This clinical study aimed to assess the impact of autologous dentin particles mixed with injectable platelet-rich fibrin (i-PRF) on a sticky tooth mixture for socket preservation in terms of consecutive need for horizontal guided bone regeneration and histological findings. Methods: Eight extraction sockets in seven patients were included in this study. Autologous dentin particles were mixed with PRF, filled in the sockets, and covered with a cross-linked collagen membrane exposed to the oral cavity and fixated by crisscross sutures. An orthopantomogram was taken before the first surgical procedure and a CBCT prior to static computer-aided implant surgery. At the time of implant placement, cores were harvested with the aid of a trephine for histological examinations for every preserved socket. Results: No further horizontal GBR intervention was required in any cases, and the histological findings were unremarkable. The new bone was mostly cancellous and in direct contact with the remaining dentin granules. Conclusions: Within the limits of this clinical study, it may be concluded that this method is valuable for socket preservation and obtaining vital and good quality bone structure. The sticky tooth technique seems to be very efficient despite the more complex equipment.